Pilot prospective open, single-arm multicentre study on off-label use of tocilizumab in patients with severe COVID-19 - Sciascia, Savino; Aprà, Franco; Baffa, Alessandra; Baldovino, Simone; Boaro, Daniela; Boero, Roberto; Bonora, Stefano; Calcagno, Andrea; Cecchi, Irene; Cinnirella, Giacoma; Converso, Marcella; Cozzi, Martina; et al. (Clinical and experimental rheumatology, 2020)
No agent has yet been proven to be effective for the treatment of patients with severe COVID-19. We conducted a pilot prospective open, single-arm multicentre study on off-label use of tocilizumab (TCZ) involving 63 hospitalised adult patients (56 males, age 62.6±12.5) with severe COVID-19. Clinical and laboratory parameters were prospectively collected at baseline, day 1, 2, 7 and 14. No moderate-to-severe adverse events attributable to TCZ were recorded. We observed a significant improvement in the levels of ferritin, C-reactive protein, D-dimer. The ratio of the partial pressure of oxygen (Pa02) to the fraction of inspired oxygen (Fi02) improved (mean±SD Pa02/Fi02 at admission: 152±53; at day 7: 283.73±115.9, at day 14: 302.2±126, p<0.05). The overall mortality was 11%; D-dimer level at baseline, but not IL-6 levels were predictors of mortality. TCZ administration within 6 days from admission in the hospital was associated with an increased likelihood of survival (HR 2.2 95%CI 1.3-6.7, p<0.05). In hospitalised adult patients with severe COVID-19, TCZ could be a safe option. An improvement in respiratory and laboratory parameters was observed. Future controlled trials in patients with severe illness are urgently needed to confirm the definite benefit with IL-6 target therapy.